Utilizing a church-based platform for mental health interventions: exploring the role of the clergy and the treatment preference of women with depression. (19th February 2021) - Iheanacho, Theddeus; Nduanya, Ujunwa Callista; Slinkard, Samantha; Ogidi, Amaka Grace; Patel, Dina; Itanyi, Ijeoma Uchenna; Naeem, Farooq; Spiegelman, Donna; Ezeanolue, Echezona E.
Abstract: Background: Training lay people to deliver mental health interventions in the community can be an effective strategy to mitigate mental health manpower shortages in low- and middle-income countries. The healthy beginning initiative (HBI) is a congregation-based platform that uses this approach to train church-based lay health advisors to conduct mental health screening in community churches and link people to care. This paper explores the potential for a clergy-delivered therapy for mental disorders on the HBI platform and identifies the treatment preferences of women diagnosed with depression. Methods: We conducted focus group discussion and free-listing exercise with 13 catholic clergy in churches that participated in HBI in Enugu, Nigeria. These exercises, guided by the positive, existential, or negative ( PEN-3 ) cultural model, explored their role in HBI, their beliefs about mental disorders, and their willingness to be trained to deliver therapy for mental disorders. We surveyed women diagnosed with depression in the same environment to understand their health-seeking behavior and treatment preferences. The development of the survey was guided by the health belief model . Results: The clergy valued their role in HBI, expressed understanding of the bio-psycho-socio-spiritual model of mental disorders, and were willing to be trained to provide therapy for depression. Majority of the women surveyed preferred to receive therapy from trained clergy (92.9%), followed by a psychiatrist (89.3%), and psychologist (85.7%). Conclusion: These findings support a potential clergy-focused, faith-informed adaptation of therapy for common mental disorders anchored in community churches to increase access to treatment in a resource-limited setting.